Wear Characteristics of Reversible Shovels of Tractor Drawn Cultivator - Chahar, V K; Tiwari, G S; Verma, R N (Journal of Agricultural Engineering, 2009)
Wear in different components in agricultural machines results in frequent stoppage of work and loss of time during peak season until replacement. Machine breakdown hampers farm operation to a great extent if failure occurs at a crucial time. Four shovels with different carbon content of 0.41, 0.50, 0.59 and 0.65% were selected and wear tests were conducted under controlled indoor circular soil bin conditions for 100 h continuously. Abrasive sand with 10-15% moisture content was used for the wear studies. Loss in weight of each shovel due to wear was recorded at an interval of 20 h. A multiple regression analysis was carried out to correlate the wear loss of shovel with its carbon content and time. Wear loss was found to increase with time in the tested range of carbon content. Shovel with maximum carbon content wore out minimum at each interval. Cumulative wear loss in shovel decreased by 37.44% with increase in carbon content from 0.41 to 0.65 per cent. The shovels with same relative hardness, but having high carbon content, were more resistant to abrasive wear. The maximum wear occurred at the tip of the shovels. Dimensional wear was measured with respect to width and thickness of shovel. Test shovels wore out along the thickness. Change in length and width of shovels was negligible as compared to their thickness. The shovel with 0.65% carbon gave the best results.